Polychlorinated Dibenzodioxins and Dibenzofurans Emissions from Transportation - Jiri Huzlik; Roman Licbinsky; Daniela Durcanska (Communications - Scientific letters of the University of Zilina, 2011)
Measurement of Persistent Organic Pollutants (POPs) was performed in order to complement the set of known emission factors. Methodology for gasoline engines emission factors determination that uses POPs concentrations measured in exhaust gasses, limited pollutants emission factors (carbon monoxide CO, nitrogen oxides NOx and hydrocarbons HC) and other compounds (carbon dioxide CO2) was elaborated. Empirical value of exhaust gasses production announced by specialists of TUV SUD was used for diesel. Emission factors of four vehicle-fuel systems were determined particularly 11 congeners of Polychlorinated Dibenzodioxins (PCDDs), 34 congeners of Polychlorinated Dibenzofurans (PCDFs) and their toxic equivalents (TEQ) for each of the measured system. TEQ PCDD/F congener profile typical for POPs sources from transportation was compiled on the basis of measured data.